Evidence of a J/ψΛ structure and observation of excited Ξ- states in the Ξ-b → J/ψΛK- decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Science bulletin, 2021)
First evidence of a structure in the J/ψΛ invariant mass distribution is obtained from an amplitude analysis of Ξb- → J/ψΛK- decays. The observed struct…